A canine adenovirus type 2 vaccine vector confers protection against foot-and-mouth disease in guinea pigs. Issue 16 (12th April 2018) - De Vleeschauwer, Annebel R.; Zhou, Xiaocui; Lefebvre, David J.; Garnier, Annabelle; Watier, Fleur; Pignon, Charly; Lacour, Sandrine A.; Zientara, Stephan; Bakkali-Kassimi, Labib; De Clercq, Kris; Klonjkowski, Bernard
Abstract: Vaccination is a key element in the control of foot-and-mouth disease (FMD). The majority of the antigenic sites that induce protective immune responses are localized on the FMD virus (FMDV) capsid that is formed by four virus-encoded structural proteins, VP1 to VP4. In the present study, recombinant canine adenovirus type 2 (CAV2)-based FMD vaccines, Cav-P1/3C R° and Cav-VP1 R°, respectively expressing the structural P1 precursor protein along with the non-structural 3C protein or expressing the structural VP1 protein of the FMDV strain O/FRA/1/2001, were evaluated as novel vaccines against FMD. A strong humoral immune response was elicited in guinea pigs (GP) following immunization with Cav-P1/3C R°, while administration of Cav-VP1 R° did not induce a satisfying antibody response in GP or mice. GP were then used as an experimental model for the determination of the protection afforded by the Cav-P1/3C R° vaccine against challenge with the FMDV strain O1 Manisa/Turkey/1969. The Cav-P1/3C R° vaccine protected GP from generalized FMD to a similar extent as a high potency double-oil emulsion O1 Manisa vaccine. The results of the present study show that CAV2-based vector vaccines can express immunogenic FMDV antigens and offer protection against generalized FMD in GP. This suggest that Cav-P1/3C R° FMDV vaccine may protect natural host species from FMD. In combination with an appropriate diagnostic test, the Cav-P1/3C R° FMDV vaccine may also serve as a marker vaccine to differentiate vaccinated from infected animals.